2003
DOI: 10.1038/sj.bjc.6600773
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA damage in non-melanoma skin cancer

Abstract: Mitochondrial DNA (mtDNA) damage, predominantly encompassing point mutations, has been reported in a variety of cancers. Here we present in human skin, the first detailed study of the distribution of multiple forms of mtDNA damage in nonmelanoma skin cancer (NMSC) compared to histologically normal perilesional dermis and epidermis. We present the first entire spectrum of deletions found between different types of skin tumours and perilesional skin. In addition, we provide the first quantitative data for the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 22 publications
2
65
0
Order By: Relevance
“…Detection of many mtDNA alterations in the premalignant or preinvasive lesions indicated that mtDNA alterations could be an early genetic event in tumorigenesis (Chen et al, 2002;Ha et al, 2002;Durham et al, 2003). Mitochondrial DNA copy number was suggested to be increased by a feedback mechanism that compensates for the defective respiratory system owing to mutated mtDNA .…”
Section: Discussionmentioning
confidence: 99%
“…Detection of many mtDNA alterations in the premalignant or preinvasive lesions indicated that mtDNA alterations could be an early genetic event in tumorigenesis (Chen et al, 2002;Ha et al, 2002;Durham et al, 2003). Mitochondrial DNA copy number was suggested to be increased by a feedback mechanism that compensates for the defective respiratory system owing to mutated mtDNA .…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients used had a mitochondrial disease. Epidermis and dermis were separated using 0.25% dispase at 4 ° C overnight (Durham et al ., 2003) and DNA was extracted using a Qiagen DNeasy (Crawley, UK) tissue extraction kit. Fibroblasts were isolated by explanting dermal skin and the outgrowing dermal fibroblasts were harvested once they approached confluence within the first 75 cm 2 flask.…”
Section: Experimental Procedures Skin and Fibroblast Samplesmentioning
confidence: 99%
“…Therefore, one might suggest that prolonged UVR exposure could either directly (by inducing base substitutions as opposed to deletions) or indirectly (by induction of free radicals) affect these 12 bp repeat structurally labile sites through opening a 'bubble' of singlestranded DNA that would enhance the recombination event, thereby eliciting an increase in mtDNA deletions. In this respect, it is of interest to note that investigation of the 3895 bp deletion in the same NMSC samples which were used in a previous study of the 4977 bp common deletion (Durham et al, 2003), showed a comparatively greater frequency of occurrence of the 3895 bp deletion. As these tumours were excised from body sites that are usually exposed to the sun, it is interesting to speculate that the 3895 bp deletion may be a more sensitive marker of cumulative sun exposure than the 4977 bp common deletion.…”
Section: Putative Mechanismmentioning
confidence: 92%
“…There are no significant age differences between the usually and occasionally sun-exposed groups (P ¼ 0.1134): two-tailed t-test (Welch correction). For all perilesional skin samples, epidermis and dermis were separated using 0.25% dispase at 41C overnight (Durham et al, 2003) and DNA was extracted using a Qiagen, DNeasy tissue extraction kit. None of the patients used for this study suffered from a mitochondrial myopathy or had a mtDNA associated neurodegenerative disease.…”
Section: Human Skin Samplesmentioning
confidence: 99%